Answer:
(4, - 2 )
Explanation:
Given the 2 equations
7x + 9y = 10 → (1)
- 2x + 6y = - 20 → (2)
Multiplying (1) by 2 and (2) by 7 and adding will eliminate the x term
14x + 18y = 20 → (3)
- 14x + 42y = - 140 → (4)
Add (3) and (4) term by term
(14x - 14x) + (18y + 42y) = (20 - 140), that is
60y = - 120 ( divide both sides by 60 )
y = - 2
Substitute y = - 2 into either of the 2 equations and solve for x
Substituting in (1)
7x + 9(- 2) = 10
7x - 18 = 10 ( add 18 to both sides )
7x = 28 ( divide both sides by 7 )
x = 4
Solution is (4, - 2 )